PENGUJIAN EMPIRIS DISIPLIN PASAR PERIODE PENJAMINAN SIMPANAN IMPLISIT DAN EKSPLISIT DI INDONESIA - Taswan Taswan (Jurnal Keuangan dan Perbankan, 2013)
This article concerned the issue of market discipline and deposit insurance in Indonesia. This research aimed toexamine the market discipline as a consequence of bank risk taking on period of implicit and explicit depositinsurance. The samples were commercial banks operating in Indonesia and they were tested using OLS regressionmodels and Sub Group analysis. It showed that market discipline functioned as a consequence of bank risktaking during the guarantee period, but there was no difference in the effect of risk on market discipline betweenperiods of implicit and explicit deposit insurance. Market discipline in Indonesia was determined more by thebank risk taking, not by the difference of deposit insurance scheme.